De O meu idioma à chave da língua: a peregrinação histórico-gramatical de Othoniel Motta - Xavier, Wendell Lessa Vilela (2012)
This thesis presents a historiographical study of the Portuguese idiom, from the analysis of grammatical works of Othoniel de Campos Motta, a grammarian of the beginning of the XX Century in Brazil. The theoretical foundation used was that of Linguistic Historiography, which considers grammar production as a historical-linguisticdiscursive document. The objective was to examine the scientific character of grammatisation produced by Othoniel Motta; identifying the main and fundamental linguistic conceptions adopted by the author, verifying the existing relation between them and the primary theoretical and textual sources utilized in his grammatisation, as well as to indicate how some of Othoniel Motta s grammatical presuppositions are identified with the linguistic normatization of the initial period of the XX Century in Brazil by examining the normative-pedagogicalpolitical character of his production and identifying the construction of a linguistic identity as part of the process of the Brazilian identity constitution. This thesis proposes that changes in the social structure constitute the product of the study of History whose aim is to interpret such changes and direct them to reality. In another sense, but in the same direction, what is variant and mutant in the idiom, according to the perspective adopted in this work, can be read from Linguistic Historiography (LH), a discipline oriented by Konrad Köerner, in an attempt to describe and explain how linguistic knowledge was acquired, formulated, communicated and developed through the ages. The grammatical works utilized in the analysis were O meu Idioma, Lições de Português e Chave da Língua, the respective prefaces, besides some articles which were also used in the demonstration of historical-linguistic instances. The demonstrated hypothesis is that Othoniel Motta was not only disseminator of a previously established model, but also participated in a transitional context which, so to speak, brought up conflicts and changes that are peculiar to the genesis of theories. The defense of a didactic-pedagogical model and the instauration of a new method the analytical, as opposed to the synthetical represented an advance in the studies of the Portuguese idiom in Brazil, taking his works into account as important contribution